Effectiveness of essential oil from the Artemisia herba-alba aerial parts against multidrug-resistant bacteria isolated from food and hospitalized patients - Abdelaziz Ed-Dra; Fouzia Rhazi Filali; Vittorio Lo Presti; Badr Zekkori; Luca Nalbone; Eman Ramadan Elsharkawy; Amar Bentayeb; Filippo Giarratana (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ed-Dra A, Filali FR, Presti VL, Zekkori B, Nalbone L, Elsharkawy ER, Bentayeb A, Giarrtana F. 2021. Effectiveness of essential oil from the Artemisia herba-alba aerial parts against multidrug-resistant bacteria isolated from food and hospitalized patients. Biodiversitas 22: 2995-3005. The World Health Organization has sounded the warning on the diffusion of multidrug resistance (MDR) bacteria, requiring solutions and alternatives to solve the therapeutic failure that may occur. This study aims to evaluate the antioxidant activity and bactericidal effectiveness against MDR bacteria of Artemisia herba-alba essential oil (A-EO) collected from semi-arid region of Morocco. Chemical composition of the A-EO was determined by Gas Chromatography-Flame Ionisation Detector and Gas Chromatography-Mass Spectrometry, while the antioxidant activity was performed by DPPH scavenging activity and ?-carotene bleaching assay. Antibacterial activity of A-EO, performed by disc diffusion assay and broth dilution method, was tested against: four MDR strains (Escherichia coli, Staphylococcus aureus, Salmonella Typhimurium and Enterococcus faecalis) isolated from food matrices, two (Klebsiella pneumonia and Pseudomonas aeruginosa) from hospitalized patients, and Escherichia coli ATCC 25922 as reference strain. Davanone was the main compound among the 17 identified. An antioxidant activity with IC50 of 1.13±0.02 mg/mL, EC50 of 2.12±0.05 mg/mL and RC50 of 0.87±0.02 mg/mL was observed. A weak activity against P. aeruginosa was observed, while it was intermediate or high against the other bacteria. This study confirms that A-EO could be a suitable alternative to antibiotics in the infection treatment related to MDR bacteria.